Derivative Action Under the Companies Act 2015: New Jurisprudence or Mere Codification of Common Law Principles? (Strathmore Law Journal, 2016)
One of the salient features of Kenya’s Companies Act 2015 is the codification of derivative action (the rule in Foss v Harbottle and its exceptions). While the statutory provision for derivative action is aimed at addressing the challenges that arose from common law derivative action, the statutory derivative action fails to achieve this outcome. At best, it is a restatement of the common law principles flowing from the rule in Foss v Harbottle and its exceptions.